EVOLUSI PARADIGMATIK KESETARAAN GENDER TERHADAP PERTUMBUHAN EKONOMI TAHUN 2018-2022 KABUPATEN/KOTA SUMATERA UTARA - Ainur Oktania; Dwi Silfani; Jeane Alisya; Eza Syahbana; Ali Asdon Tanjung; Dafa Ariza; Joko Suharianto (Politeknik Bisnis Indonesia, 2024)
This research aims to analyze the impact of gender equality on economic growth in 33 districts/cities of North Sumatra Province during the 2018-2022 period. Three dimensions of gender equality are explored, namely education (represented by Average Years of Schooling), health (represented by Life Expectancy), and employment (represented by Labor Force Participation Rate). Panel data was analyzed using the Fixed Effect Model (FEM). The findings show that gender equality in the education and health aspects has a positive and significant influence on economic growth, while gender equality in the employment aspect has a positive influence but is not statistically significant. The policy implications of this research discuss the importance of strengthening the contribution of gender equality to economic development and societal welfare. This finding is strengthened by human capital theory, health economics theory, and gender-based division of labor theory.